PENGEMBANGAN KOMIK IPA BERBASIS KARAKTER PEDULI LINGKUNGAN PADA MATERI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN (Uji Coba Siswa Kelas IV SD Muhammadiyah Kleco) - Arum Syafrilia Trisnaningsih; Ika Maryani (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
This study aims to: 1) know the development steps of IPA based on environmental character concerns on the structure and function of the pupil part IV grade elementary school, 2) to know the feasibility of science-based character-based IPA character on the material structure and function of plant part IV fourth grade. This research is a research development (Research and Development) using a model used by Robert Maribe Brance is the development of ADDIE. The subject of this research is the fourth grader of SD Muhammadiyah Kleco Kotagede Yogyakarta. Data collection techniques on product trials using teacher and student assessment questionnaires.The results showed that the assessment of media experts get the value of 83.3 with the category of "very decent". Expert assessment of the material score of 87.5 with the category "very feasible". Assessment of learning experts get the value of 95.8 with the category "very feasible". The conclusion from the researchers that the media has been feasible and effective use as a medium of learning for teachers and students of grade IV primary school.